Β-Catenin activation in fundic gland polyps, gastric cancer and colonic polyps in families afflicted by 'gastric adenocarcinoma and proximal polyposis of the stomach' (GAPPS). Issue 9 (12th July 2016) - McDuffie, Lucas A; Sabesan, Arvind; Allgäeuer, Michael; Xin, Liqiang; Koh, Christopher; Heller, Theo; Davis, Jeremy L; Raffeld, Mark; Miettienen, Markku; Quezado, Martha; Rudloff, Udo
Abstract : Aim: To evaluate possible colon involvement in the 'gastric adenocarcinoma and proximal polyposis of the stomach' (GAPPS) gastrointestinal polyposis syndrome. Methods: Prospective clinicopathological evaluation of two GAPPS families and expression of nuclear β-catenin, p53 and Ki67 measured by immunohistochemistry on endoscopic and surgical specimens from patients with GAPPS. Results: Patients with the GAPPS phenotype were more frequently affected by colonic polyps than patients at risk within the same families (p<0.01). Colonic polyps shared immunohistochemical features of fundic gland polyps and gastric cancers including increased expression of nuclear β-catenin, Ki67 and p53. Both gastric and colonic lesions harboured activating somatic variants of β-catenin signalling. Conclusions: Similarities in expression markers in fundic gland and colonic polyps, together with an enrichment of colonic adenomas in family members affected by GAPPS phenotype compared with family members at risk, support mild colonic involvement of this rare cancer syndrome. Colonoscopic screening might be warranted. Clinical Trial Registration Number: #09-C-0079; Results.